OPERATIONAL EFFICIENCY, BANKING COMPETITIVENESS, AND FINANCIAL PERFORMANCE: EVIDENCE FROM INDONESIAN BANKS (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
This study aims to examine the effect of operational efficiency and competitiveness on the financial performance of banks in Indonesia. Financial performance is proxied by Return on Assets (ROA), which reflects a bank’s ability to generate profits from its total assets. Operational efficiency is measured using the Asset Utilization Ratio (AUR), while competitiveness is measured using the Market Share. Theoretically, this study is grounded in Agency Theory to explain the relationship between operational efficiency, competitiveness, and banking financial performance. The study employs a quantitative approach using panel data from commercial banks listed on the Indonesia Stock Exchange (IDX). The data in this study are analyzed using multiple linear regression analysis to examine the effect of operational efficiency and competitiveness on the financial performance of Indonesian banks. The results show that both operational efficiency (AUR) and banking competitiveness (market share) have a positive and significant effect on financial performance (ROA).